2014
DOI: 10.14810/ijmech.2014.3409
|View full text |Cite
|
Sign up to set email alerts
|

Application of Value Stream Mapping Tool to Reduce Wastes in Bearing Industry

Abstract: In today's highly competitive business environment, companies require improvement in Production Lead Times, costs and customer service levels to survive. Because of this, companies have become more customers focused. The result is that companies have been putting in significant effort to improve their efficiency. This paper present the practical application of Value Stream Mapping (VSM) tool implement in a bearing industry. A value stream is an assortment of all actions (value added as well as non-value added)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…By using VSM we observed that non-value added time reduced and Value Stream Mapping is used to improve the plant layout. This tool is also very important for the imlementation of Kaizen technique [29]. (Buruianaet al2009) The paper explains the simulation of a Value Stream Map in a small manufacturing company before and after implementing Kaizen technique [30].…”
Section: ©Ijraset (Ugc Approved Journal): All Rights Are Reservedmentioning
confidence: 99%
“…By using VSM we observed that non-value added time reduced and Value Stream Mapping is used to improve the plant layout. This tool is also very important for the imlementation of Kaizen technique [29]. (Buruianaet al2009) The paper explains the simulation of a Value Stream Map in a small manufacturing company before and after implementing Kaizen technique [30].…”
Section: ©Ijraset (Ugc Approved Journal): All Rights Are Reservedmentioning
confidence: 99%